Gender- and age-stratified analyses of ADHD medication use in children and adolescents in Finland using population-based longitudinal data, 2008-2018 - Vuori Miika; Koski-Pirilä Anna; Martikainen Jaana E; Saastamoinen Leena (SAGE PUBLICATIONS LTD, 2022)
Aims: This study examined medication use for attention-deficit/hyperactivity disorder (ADHD) among children and adolescents by gender in Finland during 2008-2018. Methods: Aggregated data on medication use for ADHD from 2008 to 2018 were extracted from the nationwide register on reimbursed prescriptions. The annual prevalence of ADHD medication use was calculated as the number of children (6-12 years) and adolescents (13-17 years) per calendar year with at least one ADHD medication purchase divided by the number of children and adolescents in the population. Population prevalence for children was also examined by birth month. Results: In 2008, the prevalence rates for males were 1.26% in children and 0.93% in adolescents, and for females 0.21% and 0.14%, respectively. In 2018, the prevalence rates for males were 4.42% in children and 4.21% in adolescents, and for females 0.99% and 1.28%, respectively. Male-to-female ratios decreased during the study period from 6.0:1 to 4.5:1 (children) and from 6.6:1 to 3.3:1 (adolescents). ADHD medication use was more common among males and females (aged 6-12 years) born in May-August or September-December than among males and females born in January-April. Conclusions: The prevalence of ADHD medication use has continued to increase in Finland. Although use has increased more rapidly among females resulting in lower male-to-female ratios, medication use among females is considerably lower compared with males. Consequently, gender discrepancy in 2018 was relatively large, particularly among children. Future studies should also consider reporting annual prevalence by children's birth month.